Intersectional discrimination and its impact on Asian American women's mental health: A mixed-methods scoping review - Forbes, Nicola; Yang, Lauren C.; Lim, Sahnah (Frontiers in Public Health, 2023)
Introduction Gendered racism against Asian American women has become an increasing public health threat in recent years. Although intersectional discrimination (i.e., co-occurring race- and gender-based discrimination) against Asian American women is not new, research on this topic is lacking. The present scoping review sought to explore how Asian American women report experiences of intersectional discrimination through a systematic examination of the current literature. We included studies that explicitly or implicitly discuss intersectional discrimination. We also aimed to identify indicators of psychological wellbeing and coping associated with these experiences. Methods Following PRISMA Guidelines for Systematic Scoping Reviews, database searches were conducted for peer-reviewed articles. A total of 1,476 studies were title- and abstract-screened by two independent reviewers. Then, 148 articles were full-text screened for eligibility. Results A final sample of 23 studies was identified (15 qualitative and 8 quantitative). Only nine of the included studies explicitly used an intersectional framework. Results from qualitative studies revealed that Asian American women experience intersectional discrimination through fetishization, the ascription of passivity, invalidation through lack of representation and pervasive white beauty ideals, and workplace tokenization and scrutiny. Study findings suggested that Asian American women experience these forms of intersectional discrimination across multiple levels of influence (i.e., internalized, interpersonal, institutional, structural). Findings from both qualitative and quantitative studies also indicated how discrimination, whether explicitly or implicitly intersectional, contributes to adverse mental health outcomes such as body shame, disordered eating, depression, and suicidality. Studies also touched on common coping mechanisms employed by Asian American women when facing or anticipating discrimination, such as avoidance, shifting, proactive coping, and leaning on networks of support. There was a lack of studies using quantitative assessments of intersectional discrimination. Also, most studies did not include disaggregated data by ethnicity, age, sexual identity, religion, socioeconomic status, immigration status, or skin color, all of which are likely to shape their experiences. Discussion Our scoping review highlights how the marginalization of Asian American women is an urgent threat to their mental wellbeing. These findings are discussed to inform future research, interventions, and policy changes that prevent racialized and gendered violence against Asian American women.